Transformacoes na producao de graos no Brasil Meridional no periodo 1950-1979. - Sanchez, M. C.; De, L. H. (My University, 1983)
A general survey on the transformations which occurred during 1950-1979 in the cultivated area and in the yield of five agricultural products. The only significant transformation which occurred in the grain production in southern Brazil was the expansion of the soybean crop which is related to its use as an industrial raw material and as an external trade product.-after English summary
Transformation in grain yields in southern Brazil from 1950 to 1979
Keywords: Grains; ransformations in production and cultivated area.